AMBULATORY BLOOD PRESSURE PHENOTYPES, VASCULAR INFLAMMATION AND ARTERIAL STIFFNESS IN ESSENTIAL HYPERTENSION. (April 2021) - Mahmud, Azra; Alahaideb, Ruba; Alshammary, Haifa; Alfawwaz, Afnan; Abanumay, Mayar; Alhelabi, Sara; Alonazy, Amgad; Al-Zaibag, Muayed
Abstract : Objective: Hypertension is the leading risk factor for cardiovascular(CV) disease worldwide. Ambulatory blood pressure(ABPM) is the gold standard for the management of hypertension and its various phenotypes may provide prognostic information beyond clinic blood pressure (BP). The aim was to study the prevalence of various ABPM phenotypes and their relationship with target organ damage(TOD) i.e., urine albumin-creatinine ratio (ACR), and arterial stiffness as pulse wave velocity (PWV)vascular inflammation as high-sensitivity C-reactive protein(hs-CRP) in a Saudi hypertensive population. Design and method: We studied consecutive patients aged > 18 yr-old referred to the Hypertension Clinic at King Abdul Aziz Cardiac Center, Riyadh, Saudi Arabia. ABPM was performed for a 24 hour period with an oscillometric device. Masked uncontrolled hypertension (MUCH) was defined as controlled clinic BP with daytime elevated BP (definition-1); 24-hr ambulatory BP (definition-2); and either daytime or nighttime elevated BP (definition-3). Dipping was defined as a 10–20% fall in nocturnal BP; reverse-dipping as less than 0% and extreme dipping as more than 20%. The study had Institutional Ethics Committee permission. Results: The study population included 428 subjects, (mean age 53.5 ± 14 years, female = 45%). Nine percent of the population had WC; 30% had MUCH which was driven by nocturnal hypertension with higher prevalence in patients with pre-hypertension; 24 hr, 68%; daytime, 56% and nighttime 86%(p < 0.0001). Overall, 71% of the patients had MUCH which was driven by nocturnal hypertension vs. 24-hr or daytime (70%. vs. 42% vs. 32%, P < 0.0001) respectively. Eighty percent of the cohort had non-dipping with similar prevalence in MUCH and uncontrolled hypertension. Compared with controlled BP, patients with MUCH had significantly higher ACR (18.8 ± 8 vs 6.2 ± 6, p < 0.01), PWV(11.2 vs. 9.9, p < 0.001) and hs-CRP (1.6 ± 1.4 vs. 6.4 ± 2.3, p < 0.01). Conclusions: This is the first study exploring ABPM phenotypes in a Saudi hypertensive population, showing a high prevalence of MUCH in apparently well-controlled patients, driven by nocturnal hypertension and associated with prehypertension. The MUCH population had greater TOD than those with controlled BP associated with a non-dipping pattern. Our results highlight the importance of ABPM in the management of hypertension in Saudi Arabia.